The realm between eaudiobook The curse. - Grey, Phoenix (Realm Between, 2019)
Will refused to admit to the HR lady at Radical Interactive that he'd never played their debut virtual reality MMORPG The Realm. From what he'd seen in videos and heard from reviewers, the game sucked. With the company's failed attempt at entering the gaming industry, they switched their sights to focus on smaller scale educational programs. Being a beta tester for Radical Interactive was not the dream job that Will had envisioned, but he had hoped it would get his foot in the door to one day becoming a graphic designer for the company. As he filled out his new hire paperwork, he never realized that he was literally signing his life away. Now a phenomenally successful company, Radical Interactive was secretly working on something behind closed doors that would change both the medical and gaming industries forever. The Realm was reborn. The only problem was that it wasn't a game—at least not to those trapped inside.